2020
DOI: 10.3389/fcell.2020.579157
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular CIRP Induces Inflammation in Alveolar Type II Cells via TREM-1

Abstract: Extracellular cold-inducible RNA-binding protein (eCIRP) induces acute lung injury (ALI) in sepsis. Triggering receptor expressed on myeloid cells-1 (TREM-1) serves as a receptor for eCIRP to induce inflammation in macrophages and neutrophils. The effect of eCIRP on alveolar epithelial cells (AECs) remains unknown. We hypothesize that eCIRP induces inflammation in AECs through TREM-1. AECs were isolated from C57BL/6 mice and freshly isolated AECs were characterized as alveolar type II (ATII) cells by staining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“… 4 , 5 Recently, growing evidence shows that extracellular CIRP can function as a novel damage‐associated molecular pattern (DAMP) molecule that triggers proinflammatory responses. 6 , 7 , 8 In addition, blocking CIRP protein significantly increases the survival rate in a mouse hepatic ischaemia‐reperfusion model. 9 The DCD liver experiences hypotension before donation and suffers from hypothermia and hypoxia during cold storage (CS).…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 Recently, growing evidence shows that extracellular CIRP can function as a novel damage‐associated molecular pattern (DAMP) molecule that triggers proinflammatory responses. 6 , 7 , 8 In addition, blocking CIRP protein significantly increases the survival rate in a mouse hepatic ischaemia‐reperfusion model. 9 The DCD liver experiences hypotension before donation and suffers from hypothermia and hypoxia during cold storage (CS).…”
Section: Introductionmentioning
confidence: 99%
“…iCIRP has its role in regulating cellular stress responses, such as mRNA stability, cell proliferation cell survival, and tumor formation [ 21 ]. In contrast to iCIRP, eCIRP is presumed to function as a DAMP-enhancing inflammation and tissue injury [ 22 ]. eCIRP was able to induce proinflammatory cytokines through activating innate immune cells [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…AECs are an important part of the alveolar‐capillary barrier, which helps with gas exchange and protects the lung from pathogens. A recent study showed that in isolated primary AECs, mostly AEC type II (ATII) cells, treatment with rmCIRP could significantly induce cytokine IL‐6 and chemokine CXCL2 production in a dose‐dependent manner, indicating that eCIRP could induce a pro‐inflammatory phenotype in ATII cells 29 . As the migration of neutrophils requires the binding of chemokines to chemokine receptors.…”
Section: Sepsis‐associated Acute Lung Injury (Ali)mentioning
confidence: 99%